2017
DOI: 10.1186/s12864-017-3732-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient detection of viral transmissions with Next-Generation Sequencing data

Abstract: BackgroundHepatitis C is a major public health problem in the United States and worldwide. Outbreaks of hepatitis C virus (HCV) infections associated with unsafe injection practices, drug diversion, and other exposures to blood are difficult to detect and investigate. Molecular analysis has been frequently used in the study of HCV outbreaks and transmission chains; helping identify a cluster of sequences as linked by transmission if their genetic distances are below a previously defined threshold. However, HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 18 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…GHOST (Campo et al, 2015; Longmire et al, 2017; Rytsareva et al, 2017) was used to genetically characterize HCV strains and detect a transmission network. GHOST generates networks where 2 nodes representing infected individuals are linked by transmission if the minimal Hamming distance between any pair of HCV HVR1 sequences obtained from these individuals is below a relatedness threshold of 3.77% (Campo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GHOST (Campo et al, 2015; Longmire et al, 2017; Rytsareva et al, 2017) was used to genetically characterize HCV strains and detect a transmission network. GHOST generates networks where 2 nodes representing infected individuals are linked by transmission if the minimal Hamming distance between any pair of HCV HVR1 sequences obtained from these individuals is below a relatedness threshold of 3.77% (Campo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we take advantage of a complex HCV transmission network, which was recently identified among PWID in Indiana (Conrad et al, 2015; Peters et al, 2016; Ramachandran et al, 2016) using the Global Hepatitis Outbreak and Surveillance Technology (GHOST) (Campo et al, 2015; Longmire et al, 2017; Rytsareva et al, 2017), to devise and evaluate a new targeted, network-based strategy for reducing circulation and dissemination of HCV infection in 2 epidemiological settings: (1) long-established HCV infection as was observed in a PWID community during investigation in Indiana (Peters et al, 2016) and (2) a hypothetical rapid spread of a single HCV strain as observed during an outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…We used a set of 413 samples from [2] with 501.5 haplotypes per sample in average produced by NGS; 8 datatsets d 1 , ..., d 8 with 1000, 2000, . .…”
Section: Validation Datamentioning
confidence: 99%
“…Consider two sets T 1 and T 2 each containing N DNA or RNA sequences of length L. The similarity join problem consists in locating the set P of all pairs of sequences, with one sequence from T 1 and the other from T 2 , within an edit distance or Hamming distance defined by the specified threshold t. In molecular epidemiology, this computational problem needs to be solved for detection of viral transmissions from sequences of intra-host viral variants sampled from infected individuals [1,2]. Viral populations, for which the minimal inter-sample distance does not exceed the threshold, are considered to be potentially linked by transmission [1], while the number of pairs in P may suggest the time since a transmission event [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation